Preparation method of hexagonal boron nitride-based ceramic crucible
By combining hexagonal boron nitride powder with nano yttrium oxide powder, using high-temperature hot press sintering process and solid-liquid phase transformation of yttrium oxide, the problem of insufficient strength of hexagonal boron nitride ceramic materials during pressure-free sintering is solved, and a high-strength, adjustable porosity and low volatility preparation of hexagonal boron nitride-based ceramic crucible is achieved.
Patent Information
- Application Number
- CN202411907947.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-18
AI Technical Summary
During the pressure-free sintering process of hexagonal boron nitride ceramic materials, the grains form a card room structure, resulting in difficulty in densification and poor strength, which limits its application range in the industrial field. At the same time, the volatility of boron oxide affects the performance and yield of ceramic materials.
The composite powder of hexagonal boron nitride powder and nano yttrium oxide powder is adopted, and the solid-liquid phase transformation of yttrium oxide is combined with the solid-liquid phase transformation of yttrium oxide, which is filled with the hexagonal boron nitride grain pores to improve the density and strength of the material, and remove boron oxide through high-temperature heat treatment.
The high strength, adjustable porosity and low content of volatiles of hexagonal boron nitride-based ceramic crucible are achieved, which improves the mechanical properties and service life of the material, while avoiding the side effects of boron oxide.
Smart Images

Figure CN119638438A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hexagonal boron nitride ceramic material preparation, and in particular to a method for preparing a hexagonal boron nitride-based ceramic crucible. Background Art
[0002] Silicon nitride and aluminum nitride ceramic substrates have received widespread attention in the field of electronic devices due to their high thermal conductivity. At present, the preparation of substrate materials with high thermal conductivity is mainly achieved through processes such as mixing-tape casting-debinding-high-temperature sintering. During the debinding-high-temperature sintering process, the silicon nitride or aluminum nitride green body material needs to be placed in a crucible in a debinding furnace and a sintering furnace for processing and densification sintering. In order to ensure the thermal conductivity of the substrate material, the introduction of harmful elements must be controlled during the debinding and sintering process. At the same time, during the debinding process, the green body material will undergo cracking and gas will be released. In order to discharge the generated organic gas as soon as possible, the crucible needs to have a certain porosity, which is not only conducive to the release and circulation of gas during the debinding process, but also conducive to balancing the nitrogen partial pressure inside and outside the crucible during high-temperature sintering, slowing down the decomposition of ceramic materials under high temperature conditions. Among specialty ceramics, hexagonal boron nitride (HBN) ceramics have attracted widespread attention in industries such as sintering molds and crucible containers due to their high decomposition point, excellent high-temperature stability, easy processing, and low price. However, due to their low atomic diffusion coefficient and lamellar crystal structure, the hexagonal boron nitride grains form a card-house structure during pressureless sintering. This makes densification difficult and results in poor mechanical properties, thus limiting the application of HBN ceramic products in industrial fields. Furthermore, the boron nitride powder used in boron nitride crucibles has a layer of boron oxide attached to its surface. The low volatility of boron oxide causes it to volatilize and escape during the high-temperature sintering of the ceramic material in the crucible. This can cause side reactions in the ceramic material within the crucible, thereby affecting the performance and yield of the ceramic material. Therefore, the development of a high-strength crucible with adjustable porosity and low volatile content is essential for the preparation of substrate materials. Summary of the Invention
[0003] The present invention aims to provide a method for preparing a hexagonal boron nitride-based ceramic crucible, which has adjustable porosity, improved mechanical properties and low volatile matter content.
[0004] To achieve the above object, the technical solution adopted by the present invention is: A method for preparing a hexagonal boron nitride-based ceramic crucible specifically comprises the following steps: S1, ball milling hexagonal boron nitride powder and nano yttrium oxide powder respectively; S2. Weighing and mixing the two materials separately according to the volume ratio to obtain composite powder; S3, placing the composite powder of step S2 into a graphite mold, evacuating the mold and then injecting nitrogen, then heating the mold to 1450° C.-1550° C. at a first rate, then heating the mold at a second rate while applying pressure, with a holding pressure of 10 MPa-20 MPa, a holding temperature of 1750° C.-1850° C., and a holding time of 30 min-60 min, and then cooling the mold to obtain a hexagonal boron nitride-based ceramic blank; S4. The hexagonal boron nitride-based ceramic blank obtained in step S3 is subjected to mechanical processing, dust removal, and high-temperature heat treatment to obtain a hexagonal boron nitride-based ceramic crucible having a porosity of 10%-33%, a bending strength of 30 MPa-58 MPa, and a volatilization amount not exceeding 0.3% of the total weight of the crucible.
[0005] Preferably, the ball milling treatment of the hexagonal boron nitride powder in step S1 is as follows: the ball milling jar and the grinding balls are made of zirconia, the ball-to-material ratio is 2.8-3.2:1, the rotation speed is 300r / min-400r / min, and the ball milling time is 3h-4h.
[0006] Preferably, the ball milling treatment of the nano yttrium oxide powder in step S1 is as follows: the material of the ball milling jar and the grinding balls is alumina, the ball-to-material ratio is 2.8-3.2:1, the rotation speed is 300r / min-400r / min, and the ball milling time is 3h-4h.
[0007] Preferably, the volume percentage of the hexagonal boron nitride powder is 90%-97%, and the remainder is nano-yttrium oxide powder. The total volume percentage of the hexagonal boron nitride powder and the nano-yttrium oxide powder is 100%.
[0008] Preferably, the average particle size of the hexagonal boron nitride powder is 3 μm-6 μm, and the average particle size of the nano yttrium oxide powder is 400 nm-600 nm.
[0009] Preferably, the mixing in step S2 is performed in a drum mixer at a rotation speed of 100 r / min-120 r / min and a mixing time of 6 h-10 h.
[0010] Preferably, the nitrogen pressure in step S3 is 0.08 MPa-0.12 MPa.
[0011] Preferably, in step S3, the first rate is 4.5°C / min-5.0°C / min, and the second rate is 2.5°C / min-3.5°C / min.
[0012] Preferably, the pressurization speed in step S3 is 0.4 MPa / min-0.5 MPa / min.
[0013] Preferably, the high temperature heat treatment in step S4 is specifically: performing high temperature heat treatment in a vacuum furnace under temperature conditions of 1700° C. to 1800° C. and vacuum conditions for 2 h to 3 h. Beneficial effects:
[0014] The present invention introduces yttrium oxide into hexagonal boron nitride ceramics as a sintering aid. By utilizing the solid-liquid phase transition of yttrium oxide under high temperature conditions, liquid yttrium oxide is filled into the pores of hexagonal boron nitride grains. This not only promotes the densification of the hexagonal boron nitride ceramics during the sintering process, but also improves the strength of the material, thereby improving the problem of insufficient service life due to low strength.
[0015] The present invention utilizes high-energy ball milling to destroy any physical bonds between hexagonal boron nitride and nano-yttrium oxide particles, and then utilizes a mixing process to achieve physical dispersion of the hexagonal boron nitride and nano-yttrium oxide raw materials. Furthermore, by adjusting the sintering process, a hexagonal boron nitride-based ceramic body with adjustable porosity is obtained, thereby solving the problem of short service life of existing hexagonal boron nitride ceramic crucibles due to poor strength.
[0016] The present invention does not perform a deboronization treatment on hexagonal boron nitride powder before hot pressing and sintering. Instead, boron oxide is melted into liquid boron oxide during hot pressing and sintering. On the one hand, the mass transfer efficiency of boron nitride under high temperature conditions can be improved, and the growth of boron nitride grains can be promoted. On the other hand, the boron oxide can act as a sintering aid. Then, after cooling after hot pressing and sintering, the boron oxide is removed under high temperature and vacuum conditions, thereby solving the problem of the influence of the presence of volatiles on the sintering of ceramic materials and avoiding the introduction of new impurities in the step of removing the boron oxide.
[0017] The preparation method of the present invention has simple operating steps and good repeatability, and can realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a microscopic pore photograph of the hexagonal boron nitride-based ceramic crucible prepared in Example 1 of the present invention. DETAILED DESCRIPTION Example 1
[0019] This embodiment provides a method for preparing a hexagonal boron nitride-based ceramic crucible, comprising the following steps: S1. Ball milling hexagonal boron nitride powder and nano yttrium oxide powder respectively, wherein: the ball milling treatment of hexagonal boron nitride powder is as follows: the material of the ball milling jar and the grinding balls is zirconia, the ball-to-material ratio is 3:1, the rotation speed is 350r / min, and the ball milling time is 3h; the ball milling treatment of nano yttrium oxide powder is as follows: the material of the ball milling jar and the grinding balls is alumina, the ball-to-material ratio is 3:1, the rotation speed is 350r / min, and the ball milling time is 3h.
[0020] S2. Weigh the mixture separately by volume and mix it in a drum mixer at a speed of 100 r / min for 6 hours. The volume percentage of the hexagonal boron nitride powder is 90%, and the volume percentage of the nano-yttrium oxide powder is 10%. The average particle size of the hexagonal boron nitride powder is 5 μm, and the average particle size of the nano-yttrium oxide powder is 500 nm.
[0021] S3. The composite powder of step S2 is loaded into a graphite mold, vacuumed and injected with 0.1 MPa nitrogen, and then the temperature is raised to 1500°C at a heating rate of 5°C / min, and then raised to 1800°C at a heating rate of 3°C / min and kept warm for 45 minutes; and pressurization is started at 1500°C, the pressurization rate is 0.5 MPa / min, and the pressure is maintained at 15 MPa; and then cooled in the furnace to obtain a hexagonal boron nitride-based ceramic body.
[0022] S4. Take the hexagonal boron nitride-based ceramic body of step S3, and process it by wire cutting, milling machine and surface grinder according to the size of the crucible. Then, remove the dust from the machined crucible, place it in a vacuum furnace, and perform high-temperature heat treatment at 1800° C. under vacuum conditions for 3 hours to remove boron oxide in the crucible to obtain a hexagonal boron nitride-based ceramic crucible with a porosity of 24%, a bending strength of 45 MPa, and a volatilization amount not exceeding 0.3% of the total weight of the crucible. Example 2
[0023] This embodiment provides a method for preparing a hexagonal boron nitride-based ceramic crucible, comprising the following steps: S1. Ball milling hexagonal boron nitride powder and nano yttrium oxide powder respectively, wherein: the ball milling treatment of hexagonal boron nitride powder is as follows: the material of the ball milling jar and the grinding balls is zirconia, the ball-to-material ratio is 3:1, the rotation speed is 350r / min, and the ball milling time is 3h; the ball milling treatment of nano yttrium oxide powder is as follows: the material of the ball milling jar and the grinding balls is alumina, the ball-to-material ratio is 3:1, the rotation speed is 350r / min, and the ball milling time is 3h.
[0024] S2. The mixture is then weighed separately by volume and mixed in a drum mixer at a speed of 100 r / min for 7 hours. The volume percentage of the hexagonal boron nitride powder is 90%, and the volume percentage of the nano-yttrium oxide powder is 10%. The average particle size of the hexagonal boron nitride powder is 5 μm, and the average particle size of the nano-yttrium oxide powder is 500 nm.
[0025] S3. The composite powder of step S2 is loaded into a graphite mold, vacuumed and injected with 0.1 MPa nitrogen, and then heated to 1500°C at a heating rate of 5°C / min, and then heated to 1850°C at a heating rate of 3°C / min and kept warm for 30 minutes; and pressurization is started at 1500°C, with a pressurization rate of 0.5 MPa / min, and the pressure is maintained at 20 MPa; and then cooled in the furnace to obtain a hexagonal boron nitride-based ceramic body.
[0026] S4. Take the hexagonal boron nitride-based ceramic body of step S3, and process it by wire cutting, milling machine and surface grinder according to the size of the crucible. Then, remove the dust from the machined crucible, and then place it in a vacuum furnace for high-temperature heat treatment at 1750° C. under vacuum conditions for 3 hours to remove boron oxide in the crucible to obtain a hexagonal boron nitride-based ceramic crucible with a porosity of 10%, a bending strength of 58 MPa, and a volatilization amount not exceeding 0.3% of the total weight of the crucible. Example 3
[0027] This embodiment provides a method for preparing a hexagonal boron nitride-based ceramic crucible, comprising the following steps: S1. Ball milling hexagonal boron nitride powder and nano yttrium oxide powder respectively, wherein: the ball milling treatment of hexagonal boron nitride powder is as follows: the material of the ball milling jar and the grinding balls is zirconia, the ball-to-material ratio is 3:1, the rotation speed is 350r / min, and the ball milling time is 3h; the ball milling treatment of nano yttrium oxide powder is as follows: the material of the ball milling jar and the grinding balls is alumina, the ball-to-material ratio is 3:1, the rotation speed is 350r / min, and the ball milling time is 3h.
[0028] S2. The mixture is then weighed separately by volume and mixed in a drum mixer at a speed of 100 r / min for 8 hours. The volume percentage of the hexagonal boron nitride powder is 95%, and the volume percentage of the nano-yttrium oxide powder is 5%. The average particle size of the hexagonal boron nitride powder is 5 μm, and the average particle size of the nano-yttrium oxide powder is 500 nm.
[0029] S3. The composite powder from step S2 is placed in a graphite mold. After evacuation and injection of 0.1 MPa nitrogen, the temperature is raised to 1500° C. at a rate of 5° C. / min, then raised to 1800° C. at a rate of 3° C. / min and maintained at that temperature for 45 minutes. Pressurization is then initiated at 1500° C. at a rate of 0.5 MPa / min, maintained at a pressure of 15 MPa, and then cooled in the furnace to obtain a hexagonal boron nitride-based ceramic body.
[0030] S4. Take the hexagonal boron nitride-based ceramic body of step S3, and process it by wire cutting, milling machine and surface grinder according to the size of the crucible. Then, remove the dust from the machined crucible, place it in a vacuum furnace, and perform high-temperature heat treatment at 1700° C. under vacuum conditions for 2 hours to remove boron oxide in the crucible to obtain a hexagonal boron nitride-based ceramic crucible with a porosity of 30%, a bending strength of 38 MPa, and a volatilization amount not exceeding 0.3% of the total weight of the crucible. Example 4
[0031] This embodiment provides a method for preparing a hexagonal boron nitride-based ceramic crucible, comprising the following steps: S1. Ball milling hexagonal boron nitride powder and nano yttrium oxide powder respectively, wherein: the ball milling treatment of hexagonal boron nitride powder is as follows: the material of the ball milling jar and the grinding balls is zirconia, the ball-to-material ratio is 3:1, the rotation speed is 350r / min, and the ball milling time is 3h; the ball milling treatment of nano yttrium oxide powder is as follows: the material of the ball milling jar and the grinding balls is alumina, the ball-to-material ratio is 3:1, the rotation speed is 350r / min, and the ball milling time is 3h.
[0032] S2. The mixture is then weighed separately by volume and mixed in a drum mixer at a speed of 100 r / min for 1 hour. The volume percentage of the hexagonal boron nitride powder is 95%, and the volume percentage of the nano-yttrium oxide powder is 5%. The average particle size of the hexagonal boron nitride powder is 5 μm, and the average particle size of the nano-yttrium oxide powder is 500 nm.
[0033] S3. The composite powder from step S2 is placed in a graphite mold. After evacuation and injection of 0.1 MPa nitrogen, the temperature is raised to 1500° C. at a rate of 5° C. / min, then raised to 1850° C. at a rate of 3° C. / min and maintained at that temperature for 30 minutes. Pressurization is then initiated at 1500° C. at a rate of 0.5 MPa / min, maintained at a pressure of 10 MPa, and then cooled in the furnace to obtain a hexagonal boron nitride-based ceramic body.
[0034] S4. Take the hexagonal boron nitride-based ceramic body of step S3, and process it by wire cutting, milling machine and surface grinder according to the size of the crucible. Then, remove the dust from the machined crucible, and then place it in a vacuum furnace for high-temperature heat treatment at 1800° C. under vacuum conditions for 3 hours to remove boron oxide in the crucible to obtain a hexagonal boron nitride-based ceramic crucible with a porosity of 23%, a bending strength of 36 MPa, and a volatilization amount not exceeding 0.3% of the total weight of the crucible. Example 5
[0035] This embodiment provides a method for preparing a hexagonal boron nitride-based ceramic crucible, which specifically includes the following steps: S1. Ball milling hexagonal boron nitride powder and nano yttrium oxide powder respectively, wherein: the ball milling treatment of hexagonal boron nitride powder is as follows: the material of the ball milling jar and the grinding balls is zirconia, the ball-to-material ratio is 3:1, the rotation speed is 350r / min, and the ball milling time is 3h; the ball milling treatment of nano yttrium oxide powder is as follows: the material of the ball milling jar and the grinding balls is alumina, the ball-to-material ratio is 3:1, the rotation speed is 350r / min, and the ball milling time is 3h.
[0036] S2. The powders are then weighed separately by volume and mixed in a drum mixer at a speed of 100 r / min for 10 hours. The volume percentage of the hexagonal boron nitride powder is 97%, and the volume percentage of the nano-yttrium oxide powder is 3%. The average particle size of the hexagonal boron nitride powder is 5 μm, and the average particle size of the nano-yttrium oxide powder is 500 nm.
[0037] S3. The composite powder from step S2 is placed in a graphite mold. After evacuation and injection of 0.1 MPa nitrogen, the temperature is raised to 1500° C. at a rate of 5° C. / min, then raised to 1800° C. at a rate of 3° C. / min and maintained at that temperature for 45 minutes. Pressurization is then initiated at 1500° C. at a rate of 0.5 MPa / min, maintained at a pressure of 20 MPa, and then cooled in the furnace to obtain a hexagonal boron nitride-based ceramic body.
[0038] S4. Take the hexagonal boron nitride-based ceramic body of step S3, and process it by wire cutting, milling machine and surface grinder according to the size of the crucible. Then, remove the dust from the machined crucible, and then place it in a vacuum furnace for high-temperature heat treatment at 1800° C. under vacuum conditions for 3 hours to remove boron oxide in the crucible to obtain a hexagonal boron nitride-based ceramic crucible with a porosity of 27%, a bending strength of 34 MPa, and a volatilization amount not exceeding 0.3% of the total weight of the crucible. Example 6
[0039] This embodiment provides a method for preparing a hexagonal boron nitride-based ceramic crucible, which specifically includes the following steps: S1. Ball milling hexagonal boron nitride powder and nano yttrium oxide powder respectively, wherein: the ball milling treatment of hexagonal boron nitride powder is as follows: the material of the ball milling jar and the grinding balls is zirconia, the ball-to-material ratio is 3:1, the rotation speed is 350r / min, and the ball milling time is 3h; the ball milling treatment of nano yttrium oxide powder is as follows: the material of the ball milling jar and the grinding balls is alumina, the ball-to-material ratio is 3:1, the rotation speed is 350r / min, and the ball milling time is 3h.
[0040] S2. The powders are weighed separately by volume and mixed in a drum mixer at a speed of 100 r / min for 8 hours. The volume percentage of the hexagonal boron nitride powder is 97%, and the volume percentage of the nano-yttrium oxide powder is 3%. The average particle size of the hexagonal boron nitride powder is 5 μm, and the average particle size of the nano-yttrium oxide powder is 500 nm.
[0041] S3. The composite powder from step S2 is placed in a graphite mold. After evacuation and injection of 0.1 MPa nitrogen, the temperature is raised to 1500° C. at a rate of 5° C. / min, then raised to 1750° C. at a rate of 3° C. / min and maintained at that temperature for 60 minutes. Pressurization is then initiated at 1500° C. at a rate of 0.5 MPa / min, maintained at a pressure of 10 MPa, and then cooled in the furnace to obtain a hexagonal boron nitride-based ceramic body.
[0042] S4. Take the hexagonal boron nitride-based ceramic body of step S3, and process it by wire cutting, milling machine and surface grinder according to the size of the crucible. Then, remove the dust from the machined crucible, and then place it in a vacuum furnace for high-temperature heat treatment at 1750° C. under vacuum conditions for 2 hours to remove boron oxide in the crucible to obtain a hexagonal boron nitride-based ceramic crucible with a porosity of 33%, a bending strength of 30 MPa, and a volatilization amount not exceeding 0.3% of the total weight of the crucible.
[0043] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which shall fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a hexagonal boron nitride-based ceramic crucible, characterized in that: The specific steps include: S1, ball-milling the hexagonal boron nitride powder and the nano yttrium oxide powder respectively; S2, weighing separately according to volume ratio and mixing to obtain composite powder; S3, loading the composite powder of step S2 into a graphite mold, evacuating and then injecting nitrogen, then heating to 1450°C-1550°C at a first rate, then heating at a second rate while applying pressure, with a holding pressure of 10MPa-20MPa, a holding temperature of 1750°C-1850°C, a holding time of 30min-60min, and then cooling to obtain a hexagonal boron nitride-based ceramic blank; S4. The hexagonal boron nitride-based ceramic blank of step S3 is subjected to mechanical processing, dust removal and high-temperature heat treatment to obtain a hexagonal boron nitride-based ceramic crucible, wherein the porosity is 10%-33%, the bending strength is 30MPa-58MPa, and the volatilization amount does not exceed 0.3% of the total weight of the crucible.
2. The method for preparing a hexagonal boron nitride-based ceramic crucible according to claim 1, characterized in that: The ball milling treatment of the hexagonal boron nitride powder in step S1 is as follows: the material of the ball mill and the grinding balls is zirconium oxide, the ball-to-material ratio is 2.8-3.2:1, the rotation speed is 300r / min-400r / min, and the ball milling time is 3h-4h.
3. The method for preparing a hexagonal boron nitride-based ceramic crucible according to claim 1, characterized in that: The ball milling treatment of the nano yttrium oxide powder in step S1 is as follows: the material of the ball milling jar and the grinding balls is alumina, the ball-to-material ratio is 2.8-3.2:1, the rotation speed is 300r / min-400r / min, and the ball milling time is 3h-4h.
4. The method for preparing a hexagonal boron nitride-based ceramic crucible according to claim 1, characterized in that: The volume percentage of the hexagonal boron nitride powder is 90%-97%, the rest is nano yttrium oxide powder, and the total volume percentage of the hexagonal boron nitride powder and the nano yttrium oxide powder is 100%.
5. The method for preparing a hexagonal boron nitride-based ceramic crucible according to claim 4, characterized in that: The average particle size of the hexagonal boron nitride powder is 3 μm-6 μm, and the average particle size of the nano yttrium oxide powder is 400 nm-600 nm.
6. The method for preparing a hexagonal boron nitride-based ceramic crucible according to claim 1, characterized in that: The mixing in step S2 is performed in a drum mixer at a rotation speed of 100 r / min-120 r / min and a mixing time of 6 h-10 h.
7. The method for preparing a hexagonal boron nitride-based ceramic crucible according to claim 1, characterized in that: The nitrogen pressure in step S3 is 0.08MPa-0.12MPa.
8. The method for preparing a hexagonal boron nitride-based ceramic crucible according to claim 1, characterized in that: In the step S3, the first rate is 4.5°C / min-5.0°C / min, and the second rate is 2.5°C / min-3.5°C / min.
9. The method for preparing a hexagonal boron nitride-based ceramic crucible according to claim 1, characterized in that: The pressurization speed in step S3 is 0.4 MPa / min-0.5 MPa / min.
10. The method for preparing a hexagonal boron nitride-based ceramic crucible according to any one of claims 1 to 9, characterized in that: The high temperature heat treatment in step S4 is specifically: performing high temperature heat treatment in a vacuum furnace under a temperature condition of 1700° C.-1800° C. and a vacuum condition for 2 h-3 h.
Citation Information
Cited By
Special low-carbon fire-resistant ceramic crucible for high-temperature alloy casting and preparation method of special low-carbon fire-resistant ceramic crucible
CN121135434A